New methods for ranking milking farms with respect to the development of rearing technology and work efficiency - Kovács, Sándor; Sipos, László; Vántus, András (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
The major goal of milking farms to achieve and maintain competitiveness. Rearing tehnology and basic conditions of production have a major influence on the expensive work-time input and on the quantity of the porducts produced. Up-to-date production conditions can reduce the work-time input, consequently the thechnological improvement of milking farms is advisable. For this reason, authors have examined 10 milking farms over a 10-years period considering the amount spent on technological improvement and the labour productivity indices and their change. Based on these factors farms were than ranked by the Sum of Ranking Difference method. According to the multivariable ranking, the benchmark farm can be selected and its rearing technology can be described. Infromation obtained from this examination could help other farms to be more successful and compatitive. On the other hand, milking farms were also segmented into several clusters by using novel multivariable methods and the revealed clusters have been described by the studied factors.
Keywords: dairy farm; rearing technology; developments; ranking; clustering